Literature Studies on Maintenance Management - Soesatijono Soesatijono; Mahros Darsin (University of Muhammadiyah Malang, 2021)
The purpose of this paper is to review from early days until recent time the development of maintenance management methods from maintenance textbooks to give a glance view for researcher and practitioner where maintenance start until recent development and practical application of maintenance management. The methodology approach is by reviewing an early age maintenance management, maintenance management on eighties, maintenance management on nineties and recent maintenance management. Comparing and categorizing maintenance management methods along with time will increase knowledge how to choose the right maintenance for practical application. From this review it found that the paper also revealed from time to time, maintenance management adapt and improve to gain more sustainable maintenance, including the new shift of paradigm of maintenance itself. The originality and contribution of this research is that the paper contains many maintenance management methods from maintenance textbooks, maintenance management methods elaborated in an easy way. Therefore, the importance of maintenance management could be properly understood. For further study, the paper suggest that research needed to study or apply on methods found in this paper on practical application whether will give a proper result or just nice on theoretical only.